Insights into Spanish Geography Education - Bagoly-Simó, Péter (Journal of Geography Education, 2020)
Zeitschrift für Geographiedidaktik | Journal of Geography Education (ZGD) continues to serve as the flagship journal of Geography Education in Germany. Therefore, its content may be considered a seismograph of debates in the discipline. Over time, the journal's profile remained sensitive to the discipline’s theoretical, methodological, and applied challenges.